2016
DOI: 10.1039/c6ra02864k
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glassing solvent deuteration and Gd3+ doping on 13C DNP at 5 T

Abstract: We report the influence of glassing solvent deuteration and Gd 3+ doping on 13 C dynamic nuclear polarization (DNP) nuclear magnetic resonance (NMR) performed on [1-13 C] sodium acetate at B 0 ¼ 5 T and 1.2 K. Our data reveal that at 5 T, glassing solvent deuteration still results in a 40% improvement of the 13 C DNP signal when a large electron spin resonance (ESR) linewidth 4-oxo-TEMPO free radical is used, but results in a 60% decrease of the DNP signal in the case of a sample doped with small ESR linewidth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(62 citation statements)
references
References 36 publications
7
55
0
Order By: Relevance
“…Similar to sample preparation described before, [29] 100 μL aliquots of 3 M [1- G. 13 C microwave frequency sweeps and 13 C solid-state polarization measurements…”
Section: Dnp Sample Preparationmentioning
confidence: 99%
“…Similar to sample preparation described before, [29] 100 μL aliquots of 3 M [1- G. 13 C microwave frequency sweeps and 13 C solid-state polarization measurements…”
Section: Dnp Sample Preparationmentioning
confidence: 99%
“…Similar to previous studies of Gd 3+ in DNP, Tb 3+ and Dy 3+ doped samples resulted in DNP spectra that had P(+) and P( ) shifted toward each other. 36,60 At the optimum concentration of Dy 3+ -DOTA (1.5 mM), both positive and negative polarization peaks were shifted by 20 MHz from the reference sample. This shift was consistent over all concentrations of Dy studied, only increasing to 25 MHz for both peaks with 4 mM Dy.…”
Section: B 13 C Solid State Polarizationmentioning
confidence: 99%
“…[31][32][33] Meanwhile, the trityls, particularly OX063, which have some of the narrowest EPR linewidths among free radicals, were found to be excellent polarizing agents for low-γ nuclei like 13 C. 16,34 When using these radicals, DNP enhancements may be improved further by the addition of trace amounts of gadolinium. [34][35][36][37] Recently, it was found that the addition of holmium to a trityl-doped sample results in liquid state enhancement similar to that achieved by using gadolinium. 38 While the use of these lanthanides may lead to significant polarization gains, the free ion form of these lanthanides may lead to greater toxicity of the DNP sample, which must be considered prior to in vivo biomedical application.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations